The Studying the Need for Further Study a Master’s Degree in Computer and Educational Technology Faculty of Education, Nakhon Phanom University - Khotpratoom, Phongthep; Sangboonraung, Watcharee; Jarutkamolpong, Suwisa; Kweangmuang , Parama; Daungtod, Srisuda (International Journal of Educational Communications and Technology, 2022)
The aim of the research was to study the need for further study of a master’s degree in computer and educational technology Faculty of Education Nakhon Phanom University. A questionnaire was used to conduct the survey, which was given to a random sample of 400 participants including teacher, educational personnel, final year undergraduate students and fresh graduates from Nakhon Phanom, Mukdahan, and Bueng Kan provinces. Analyze the data by finding the percentage, mean, standard deviation and one-way ANOVA. The study found statements on the need of establishing a master’s degree, 310 participants (77.50%) and the importance of the education curriculum. Computer and Educational Technology most of the respondents expressed their opinion that they helped develop the organization, 190 participants (47.50%) followed by helping to improve the quality of life of 127 participants (31.80%). Gender, age, domicile, education degree, work experience and affiliation do not affect the decision to study further.